India’s Higher Education and COVID-19: Responses and Challenges - Mathews, Eldho (International Higher Education, 2020)
The impact of COVID-19 underscores the importance of developing a detailed crisis management plan and ensuring equity while promoting digital education in Indian higher education. The flow of Indian students to institutions outside the country is likely to drop if the existing situation does not improve within a few months.